Respuesta :
Answer:
- x = -2 is an extraneous solution of [tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex]
- [tex]x = 7[/tex] is the solution of [tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex].
Step-by-step explanation:
As the given expression
[tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex]
Lets solve this expression
[tex]\frac{3}{(x+3)(x+2)}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex]
Multiply all terms by (x+2)(x+3) and cancel:
[tex]3+(x-1)(x+3)=7(x+2)[/tex]
[tex]x^{2} +2x=7x+14[/tex]
[tex]x^{2} +2x-(7x+14)=7x+14-(7x+14)[/tex]
[tex]x^{2} -5x-14=0[/tex]
[tex](x+2)(x-7)=0[/tex]
[tex]x+2=0[/tex] or [tex]x-7=0[/tex]
[tex]x = -2[/tex] or [tex]x = 7[/tex]
x = -2 is an extraneous solution while [tex]x = 7[/tex] is the right solution.
Verification:
Check answers. (Plug them in to make sure they work.)
Putting [tex]x = -2[/tex]
[tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex]
[tex]\frac{3}{(-2)^2+5(-2)+6}+\frac{(-2)-1}{(-2)+2}=\frac{7}{(-2)+3}[/tex]
[tex]\frac{3}{4-10+6}+\frac{-3}{0}=\frac{7}{1}[/tex]
[tex]\frac{3}{0}+\frac{-3}{0}=\frac{7}{1}[/tex]
∞ + ∞ = 7
L.H.S ≠ R.H.S
x = -2 is an extraneous solution.
Putting [tex]x = 7[/tex]
[tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex]
[tex]\frac{3}{(7)^2+5(7)+6}+\frac{(7)-1}{(7)+2}=\frac{7}{(7)+3}[/tex]
[tex]\frac{3}{49+35+6}+\frac{6}{9}=\frac{7}{10}[/tex]
[tex]\frac{3}{90}+\frac{6}{9}=\frac{7}{10}[/tex]
[tex]\frac{3+60}{90}=\frac{7}{10}[/tex]
[tex]\frac{63}{90}=\frac{7}{10}[/tex]
[tex]\frac{7}{10}=\frac{7}{10}[/tex]
L.H.S = R.H.S
So, [tex]x = 7[/tex] is the solution of [tex]\frac{3}{x^2+5x+6}+\frac{x-1}{x+2}=\frac{7}{x+3}[/tex].
Keywords: solution, extraneous solution, equation
Learn more about solution, extraneous solution of equation from brainly.com/question/12833402
#learnwithBrainly